2001
DOI: 10.1046/j.1523-1739.2001.015003617.x
|View full text |Cite
|
Sign up to set email alerts
|

Plant‐Mammal Interactions in Tropical Bolivian Forests with Different Hunting Pressures

Abstract: We studied plant‐animal interactions and vegetation structure in two geographically close tropical Bolivian forests subjected to different hunting intensities. We hypothesized that reduction of mammals openface> 1 kg in an “intensively hunted forest,” compared with an “occasionally hunted forest,” should correlate with decreased seed predation and seedling trampling, increased seedling survival and density, and decreased tree‐species diversity at the seedling stage in relation to the adult stage. The occasiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
85
1
12

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(101 citation statements)
references
References 11 publications
3
85
1
12
Order By: Relevance
“…observ.). Most of the seeds and seedlings of any species in areas disturbed by rooting were killed (Roldán, & Simonetti, 2001;Aliaga-Rossel, pers. observ.).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…observ.). Most of the seeds and seedlings of any species in areas disturbed by rooting were killed (Roldán, & Simonetti, 2001;Aliaga-Rossel, pers. observ.).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the effects of medium size rodents are difficult to determine and may depend on the composition and density of species within the forest (Donatti et al, 2009). Different forests close to human settlements will have different degrees of changes in wildlife composition, and such variation should result in different seed removal patterns and survivorship, causing changes in the dynamics of Astrocaryum seed removal across different scales within patches (i.e., near higher adult density) and ultimately influencing the structure and the composition of the local forest (Roldán, & Simonetti, 2001;Beckman, & Muller-Landau, 2007;Donatti et al, 2009;Holbrook, & Loiselle, 2009 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of mammal populations on seed dispersal and seed predation can be evaluated in several ways, including comparisons of seed and seedling survival where different levels of hunting have occurred, or exclosure experiments that eliminate different size categories of seed or seedling predators. When seeds are protected from mammalian access, there may result a secondary effect of increased seedling recruitment (Dirzo and Miranda, 1991;Wright et al, 1999) or decreased seedling recruitment (Asquith et al, 1997;Roldan and Simonetti, 2001), depending upon the relative importance of seed predation versus seed dispersal by the excluded mammals (Brewer et al, 1997;Beckman and Muller-Landau, 2007). …”
Section: Structure Of Mammalian Communitiesmentioning
confidence: 99%
“…Pacas are found in mangroves, semideciduous forests, riparian vegetation and sites with dense undergrowth, always near water sources (Pérez 1992;Guzmán-Aguirre 2008;Wallace et al 2010). They tolerate, and even do better in non-intensively-cultivated land (Roldán and Simonetti 2001;Guzmán-Aguirre 2008;Parroquin et al 2010). Using tracks and fecal surveys at Sierra Tabasco, Mexico, Guzmán-Aguirre (2008) found that pacas prefer primary forest over secondary forests and fallows; he never found paca signs in croplands.…”
Section: Introductionmentioning
confidence: 99%